2009
DOI: 10.1163/157181109x427734
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Participation in Elective Bodies: The Maori in New Zealand

Abstract: Th e article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…These arguments were acknowledged by the Royal Commission (1986), which found that for many Mäori the seats were considered an important expression of their position as tangata whenua; and by the Mäori Electoral Option Report (Waitangi Tribunal, 1994, s. 3.1), which suggested that the seats were considered to be an exercise-although limited-of the tino rangatiratanga guaranteed to Mäori under the Treaty (see also Xanthaki & O'Sullivan, 2009). More recently, the Constitutional Advisory Panel (2013) similarly reported that some submissions considered the Mäori seats to be a significant, although not necessarily sufficient, symbol of commitments made by iwi and the Crown at Waitangi; and that they ensured a distinctive Mäori voice in the issues considered by Parliament.…”
Section: Proportional Representation and The "Need" For The Mäori Seatsmentioning
confidence: 99%
See 3 more Smart Citations
“…These arguments were acknowledged by the Royal Commission (1986), which found that for many Mäori the seats were considered an important expression of their position as tangata whenua; and by the Mäori Electoral Option Report (Waitangi Tribunal, 1994, s. 3.1), which suggested that the seats were considered to be an exercise-although limited-of the tino rangatiratanga guaranteed to Mäori under the Treaty (see also Xanthaki & O'Sullivan, 2009). More recently, the Constitutional Advisory Panel (2013) similarly reported that some submissions considered the Mäori seats to be a significant, although not necessarily sufficient, symbol of commitments made by iwi and the Crown at Waitangi; and that they ensured a distinctive Mäori voice in the issues considered by Parliament.…”
Section: Proportional Representation and The "Need" For The Mäori Seatsmentioning
confidence: 99%
“…Since 1993, the total Mäori enrolments in the Mäori Electoral Option have increased steadily, raising the number of seats to seven. However, it is also worth noting that around half of eligible Mäori choose to not enrol on the Mäori roll (Xanthaki & O'Sullivan, 2009). The choice that is provided to Mäori voters by the electoral option is markedly different to that offered to voters in majority-minority districts in the United States.…”
Section: Individual Equality and Autonomymentioning
confidence: 99%
See 2 more Smart Citations
“…With a reformed electoral system, this number rose to 13.5% in 1996 and to 16.5% by 2005. 37 Based on this evidence, the opportunity the increased representation of women in Canada via electoral reform is an available and realistic solution.…”
mentioning
confidence: 99%